EFFECT OF PROCESS PARAMETERS ON HARDNESS, DEPTH OF HEAT AFFECTED ZONE AND MICRO STRUCTURE OF WELDMENT IN MIG WELDING (Journal of Mechanical Engineering, 2015)
Electrode wire diameter, welding current, electrode wire feed rate, arc length are influential processparameters for hardness, depth of heat affected zone and microstructure of weldment in case of MIG weldingprocess. In this work, the effect of these process parameters on weldment characteristics had been studied.Experiments were conducted using bead-on surface of medium carbon steel plate in a semi-automatic MIGwelding machine. Hardness, depth of heat affected zone and microstructure of weldment were examined. Anartificial neural network (ANN) based modeling of the experiments had been successfully done to realize thepatterns of results obtained from the experiments. It had been observed that the microstructures obtained inthese weldments were distinctly different from that of the base metal. Microstructures, hardness and depth ofheat affected zone of weldment depends on the process parameters. ANN model shows good agreement with theexperimental results in case of hardness and depth of heat affected zone of weldment.